PENGARUH (P5) TEMA GAYA HIDUP BERKELANJUTAN TERHADAP DIMENSI GOTONG ROYONG MELALUI BUDIDAYA TANAMAN OBAT KELUARGA - Siti Roudlotul Hikamah; Fatma Sukmawati Ningsih; Miftahul Hakim (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Every child is born with inherent potential, and schools play a crucial role in optimizing this potential. This study aims to examine the influence of the Pancasila Student Profile Strengthening Project (P5) with a sustainable lifestyle theme on the dimension of mutual cooperation through the cultivation of Family Medicinal Plants (Tanaman Obat Keluarga or TOGA). The project was implemented once a week over a three-month period involving 33 seventh-grade students from class VII-D. The research employed a quantitative approach with a quasi-experimental one-group pretest–posttest design. Data were analyzed using the Wilcoxon test with the assistance of SPSS version 25. The observation instrument was adapted from the 2024 P5 Guideline Book published by the Ministry of Education and Culture (Kemendikbud). The results showed a significance value of 0.000 (p < 0.05), indicating that the P5 activity through TOGA cultivation significantly influenced students’ character development, particularly in fostering mutual cooperation and a sense of responsibility among peers. These findings suggest that this approach is effective and feasible as an alternative method to enhance students’ character education within the learning process.